Assessment of Interleukin-21 Gene Polymorphisms and Protein Level in Rheumatoid Arthritis among Egyptians - Elfasakhany, Fathy M.; Alqahtani, Mashael S.; Elfasakhany, Ahmed F.; Elguindy, Ayman M. A. (Open Access Macedonian Journal of Medical Sciences, 2025)
BACKGROUND: Rheumatoid Arthritis (RA) is characterized by joint damage, persistent inflammation, and producing autoantibodies. Interleukin 21 (IL-21) and its receptor (IL 21R) have an important function in the pathogenesis of RA. High serum level of IL-21 has been related to RA and disease activity. AIM: Here, we assessed the relationship of IL-21 polymorphisms and IL-21 serum levels with RA among Egyptians. METHODS: DNA was separated from peripheral blood of 120 healthy controls and 120 patients with RA and genotyped for two single nucleotide polymorphisms of the IL-21 gene (rs2055979 and rs2221903) using polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) technique. IL-21 serum level was assessed by ELISA. RESULTS: The IL-21 rs2055979 AA genotype and A allele were higher in RA patients than in the control group (p =0.005, OR=2.657, 95% CI=1.333-5.293 and p =0.019, OR=1.932, 95% CI=1.112-3.356 respectively). The serum levels of anti-CCP, IL-21, Rheumatoid factor, C-reactive protein and ESR were higher in RA subjects in comparison to the controls (p <0.0001). Furthermore, IL-21 serum level was higher in AA genotype of RA patients in comparison to the CC and CA genotypes (p <0.001 and 0.041 respectively). The IL21 rs2221903 genotypes and alleles were statistically indifferent between the studied groups. CONCLUSIONS: IL-21 rs2255979 polymorphism is associated with the susceptibility to RA in Egyptian subjects. Moreover, the elevated IL-21 levels and its association with AA genotype in RA patients indicate its importance in the pathogenesis of RA. This means that IL-21 might be used as genetic marker and would have therapeutic application in RA.